Can we make development training developmental? - Mann, Pete (1999)
This article questions whether the requirements demanded for effective performance in the field of development are sufficiently addressed through training that traditionally emphasizes acquisition of intellectual competence from knowledge articulated in instruction-led teaching. Casting the task in development training as the strengthening of the capacity of practise, the author asks what kind of purpose, approach and focus in learning best responds to the demands of practitioners working in the difficult circumstances of the unknown. Three core concepts are introduced as underpinning an emphasis in development training that makes learning developmental: meta goals, experience-based problem solving and tacit knowledge. The conceptual interrelationship of all three concepts bridges the gulf in practitioner development of the conflicting thought worlds between the tacit practice of development and the explicit understanding of that practice. - Reproduced
Keywords: Training